Comparison of the accuracy of contact force measurement in four commercially available force-sensing ablation catheters. (19th May 2022) - Kueffer, T; Haeberlin, A; Knecht, S; Baldinger, SH; Servatius, H; Madaffari, A; Seiler, J; Muehl, A; Franzeck, F; Asatryan, B; Noti, F; Tanner, H; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Contact force-sensing catheters are widely used for ablation of cardiac arrhythmias. They allow precise quantification of catheter-to-tissue contact, which is an important determinant of lesion size and durability. Moreover, contact force information reduces the risk for cardiac perforation and is used for estimation of lesion size. However, the accuracy of contact force sensors across different manufacturers has not been validated independently. Objective: To compare the accuracy and reproducibility of different force sensing catheters used in cardiac electrophysiology procedures. Methods: A force measurement setup containing a heated saline water bath and a catheter fixation mechanism was constructed. The setup allows to accurately measure forces applied to a platform with the catheter. We studied four different catheter models, equipped with the following, unique force-measurement technologies (figure 1): 1) multiple-fiber optical sensor; 2) single-fiber optical sensor; 3) inductive sensor; and 4) magnetic field sensors. For each model, we assessed three catheters. Repeated measurements within the force range of 0g to 60g and at electrode-tissue contact angles of 0°, 45°, and 90° were performed and validated against the force measurement unit of our measurement setup. Results: For each catheter, at least 500 measurements at different contact forces (equally distributed across the measurement range of 0 to 60 grams) were performed. Correlation of measured-force to real-force was ρSpearman=0.99 for MFOS, ρSpearman=0.98 for SFOS, ρSpearman=0.99 for IS, and ρSpearman=0.98 for MFS. MFS and SFOS showed a higher variance for high forces and increased intra-catheter variability compared to MFOS and IS. IS overestimated higher contact force at 0° and 30°. MFS and SFOS underestimated contact force for higher forces at 30° and 45° (figure 2). Within a clinical range of 5g to 40g, the catheters reached the following root-mean-square-error, independent of contact angle: MFOS 0.88g ±0.68g, SFOS 2.15g ±1.74g, IS 0.88g ±0.72g, and MFS 1.13g ±1.01g. Conclusion: Measured contact by force-sensing catheters correlates well with true exerted electrode-tissue force. Despite an excellent overall correlation, some technologies may be prone to significant errors at higher forces (>10g under-/overestimation of true contact force) with potential clinical consequences related to increased risk of perforation.